Fill in the blanks:

(i) $$\dfrac {-4}{13} – \dfrac{-3}{26}$$ = …

(ii) $$\dfrac {-9}{14}$$+ …. = -1

(iii) $$\dfrac {-7}{9}$$+ …. =3

(iv) … + $$\dfrac {15}{23}$$ = 4

Asked by Aaryan | 1 year ago |  66

Solution :-

(i)  $$\dfrac{ -4}{13} – \dfrac{-3}{26}$$

Let us take LCM for 13 and 26 which is 26

$$\dfrac{ (-4×2 + 3×1)}{26}$$

$$\dfrac{(-8+3)}{26} = \dfrac{-5}{26}$$

(ii) Let us consider the number to be added as x

$$\dfrac{-9}{14} + x = -1$$

x = $$-1 + \dfrac{9}{14}$$

By taking LCM as 14 we get,

$$x =\dfrac{ (-1×14 + 9)}{14}$$

= $$\dfrac{ (-14+9)}{14}$$

$$\dfrac{-5}{14}$$

(iii) Let us consider the number to be added as x

$$\dfrac{ -7}{9} + x = 3$$

$$x = 3 +\dfrac{7}{9}$$

By taking LCM as 9 we get,

$$x = \dfrac{(3×9 + 7)}{9}$$

= $$\dfrac{ (27 + 7)}{9}$$

$$\dfrac{34}{9}$$

(iv) Let us consider the number to be added as x

$$x + \dfrac{15}{23} = 4$$

$$x = 4 – \dfrac{15}{23}$$

By taking LCM as 23 we get,

$$x = \dfrac{(4×23 – 15)}{23}$$

= $$\dfrac{ (92 – 15)}{23}$$

=$$\dfrac{77}{23}$$

Answered by Aaryan | 1 year ago

Related Questions

By what number should 1365 be divided to get 31 as quotient and 32 as remainder?

By what number should 1365 be divided to get 31 as quotient and 32 as remainder?

Which of the following statement is true / false?

Which of the following statement is true / false?

(i) $$\dfrac{ 2 }{ 3} – \dfrac{4 }{ 5}$$ is not a rational number.

(ii) $$\dfrac{ -5 }{ 7}$$ is the additive inverse of $$\dfrac{ 5 }{ 7}$$

(iii) 0 is the additive inverse of its own.

(iv) Commutative property holds for subtraction of rational numbers.

(v) Associative property does not hold for subtraction of rational numbers.

(vi) 0 is the identity element for subtraction of rational numbers.

If x = 4 / 9, y = – 7 / 12 and z = – 2 / 3, then verify that x – (y – z) ≠ (x – y) – z

If x = $$\dfrac{4 }{ 9}$$, y =$$\dfrac{-7 }{ 12}$$ and z = $$\dfrac{-2 }{ 3}$$, then verify that x – (y – z) ≠ (x – y) – z

If x = $$\dfrac{ – 4 }{ 7}$$ and y = $$\dfrac{2 }{ 5}$$, then verify that x – y ≠ y – x
Subtract the sum of $$\dfrac{ – 5 }{ 7} and\dfrac{ – 8 }{ 3}$$ from the sum of $$\dfrac{5 }{ 2} and \dfrac{– 11 }{ 12}$$